2011
DOI: 10.1016/j.cell.2011.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Inheritance of an Acquired Small RNA-Based Antiviral Response in C. elegans

Abstract: Induced expression of the Flock House virus in the soma of C. elegans results in the RNAi-dependent production of virus-derived, small interfering RNAs (viRNAs), which in turn silence the viral genome. We show here that the viRNA-mediated viral silencing effect is transmitted in a non-Mendelian manner to many ensuing generations. We show that the viral silencing agents, viRNAs, are transgenerationally transmitted in a template-independent manner and work in trans to silence viral genomes present in animals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
325
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 323 publications
(338 citation statements)
references
References 37 publications
1
325
1
2
Order By: Relevance
“…Each nematode produces hundreds of progeny, and therefore small RNAs must be amplified to overcome the transgenerational dilution effect that expands logarithmically. Indeed, in worms which are mutants for the RdRP RRF-1, inherited RNAi diminishes after 2 generations, indicating the RNA amplification is required for long-term transgenerational RNAi effects [21,24]. In addition, it was recently demonstrated that the RRF-1 RdRP is required for effective transgenerational targeting of chromatin [25].…”
Section: Rna-mediated Gene Silencing and Inheritancementioning
confidence: 99%
See 4 more Smart Citations
“…Each nematode produces hundreds of progeny, and therefore small RNAs must be amplified to overcome the transgenerational dilution effect that expands logarithmically. Indeed, in worms which are mutants for the RdRP RRF-1, inherited RNAi diminishes after 2 generations, indicating the RNA amplification is required for long-term transgenerational RNAi effects [21,24]. In addition, it was recently demonstrated that the RRF-1 RdRP is required for effective transgenerational targeting of chromatin [25].…”
Section: Rna-mediated Gene Silencing and Inheritancementioning
confidence: 99%
“…Small RNAs targeting viral genomes (viRNA) accumulate in wild type infected worms, but not mutant worms [35,36]. Moreover, it was shown that viRNAs are capable of being transmitted between generations of worms [21,24]. RNAi heterozygous mutant worms, which are functionally competent, can generate anti-viral RNAi immunity that protects their homozygous RNAi-mutant progeny from replication of a transgenic Flock House Virus (FHV) for multiple generations [21].…”
Section: Inherited Anti-viral Immunitymentioning
confidence: 99%
See 3 more Smart Citations